Magnetic and superconducting instabilities in the periodic Anderson model: a random-phase-approximation study - Peres, Nuno (2020)
We study the magnetic and superconducting instabilities of the periodic Anderson model with infinite Coulomb repulsion U in the random-phase approximation. The Neel temperature and the superconducting critical temperature are obtained as functions of electronic density (chemical pressure) and hybridization V (pressure). It is found that close to the region where the system exhibits magnetic order the critical temperature T-c is much smaller than the Neel temperature, in qualitative agreement with some T-N/T-c ratios found for some heavy-fermion materials. In our study, the magnetic and superconducting physical behaviour of the system has its origin in the fluctuating boson fields effecting the infinite on-site Coulomb repulsion among the f electrons.